What evidence exists on the pathways linking climate change to livestock production and consumption in sub-Saharan Africa? A protocol for a systematic map - Tareke, Amare Abera; Zerfu, Taddese Alemu; Hailesilassie, Wondimu Tadiwos; Bosire, Caroline K.; Mukherji, Aditi (CGIAR Climate Change Impact Platform, 2024)
Climate change is increasingly recognized as a significant threat to agricultural systems worldwide, with profound implications for livestock production and consumption. With its heavy dependence on livestock for food security, income, and cultural practices, Sub-Saharan Africa (SSA) is particularly vulnerable to climate change’s impacts. However, the pathways through which climate change affects livestock systems in this region remain insufficiently explored. This protocol outlines a systematic map to identify, catalogue, and visualize the available evidence on these pathways. The goal of the incoming systematic map is to provide a comprehensive overview of existing evidence on how climate change is influencing livestock production and consumption in SSA, while also identifying key gaps in the current literature. The map will help to identify evidence on key pathways through which climate change impacts livestock systems and the broader agricultural sector in the region. To ensure comprehensive coverage, we will conduct an exhaustive search across multiple bibliographic databases including Web of Science, Scopus, CAB Abstracts, and PubMed - along with organizational websites, web-based searches, and citation snowballing to capture all relevant studies. The search will be carried out in English and will focus on SSA contexts wherever applicable, ensuring that the findings are directly relevant to the region’s unique challenges. The search results will be imported into Rayyan, a systematic review tool, where studies will be screened for relevance based on title, abstract, and full text. At each stage of the screening process, the number of studies included and excluded will be recorded, and the reasons for exclusion during full-text screening. Key metadata from the selected studies—such as bibliographic information, study characteristics, and the exposure and outcome components related to climate change, livestock production, and consumption—will be coded. The findings will be summarized using narrative summaries, heat maps, and an evidence atlas, providing a visual representation of existing knowledge and highlighting critical gaps that require further investigation.